Impact of Various Acids and Bases on the Voltammetric Response of Platinum Group Metal Oxides - Sebastian Chalupczok; Peter Kurzweil; Helmut Hartmann (International Journal of Electrochemistry)
The voltammetric response of platinum metal oxides is discussed with respect to novel pH sensors combining both miniaturization and stability. For practical applications in solutions of any kind, for example, in tap water and in domestic sewage, various interferences must be considered, such as chloride and reducing agents. This work clarifies the voltammetric behavior of RuO2 electrodes in solutions of different pH values and ionic strengths.